PENERAPAN PENDEKATAN SAINTIFIK BERORIENTASI METODE GUIDED DISCOVERY LEARNING UNTUK MENINGKATKAN KETERAMPILAN PROSES SAINS SISWA PADA MATA PELAJARAN BIOLOGI KELAS XI MIA 2 SMA BABUSSALAM PEKANBARU TAHUN PELAJARAN 2014/2015 - Dewi Nilam Sari Nilam Sari; Mariani Natalina Linggasari Natalina Linggasari Linggasari; Evi Suryawati Suryawati (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2015)
Abstract : The purpose of this research is to increase student science skill process by applied scientific approach oriented guided discovery learning method in class XI of MIA 2 SMA Babussalam Pekanbaru in academic year 2014/2015. This research was classroom action research in two cycles and consist of plan, action and observation, and reflection. Data was collected in this research was science skill process in three aspect those were cognitive, affective and psychomotor. The data was collected using test and observation. The result of this research showed an increase for every aspect of science  process skills. Science skill process in cognitive aspect that was seen from test result in cycle I was 3.07 (B) and increase in cycle II, that was 3.16 (B). The students passing studying in cycle I was 19 (63.33%) and increased in cycle II became 25 (83.33%). The average of affective aspect in cycle I was 2.96 (good) increased in cycle II that was 3.49 (good). Science skill process in psychomotor aspect was 2.87 (B) in cycle I and became 3.46 (B+) in cycle II. The conclusion of this research was applied scientific approach oriented guided discovery learning method can increase student science skill process in class XI of MIA 2 SMA Babussalam Pekanbaru in academic year 2014/2015. Key words : scientific approach, guided discovery learning method, science skill process